Workshop Persiapan Sertifikasi Ahli K3 Umum oleh Politeknik LP3I Jakarta Bekerjasama Dengan Lembaga Competence Development Center (CDC) LP3I Secara Daring - Kaban, Karya Bakti; Rahmadhani, May Vitha; Sirait, Edison P.; Zulfikar, Ali; Permana, Amon Gari (Yayasan Daarul Huda Kruengmane, 2024)
Certification and appointment as a General K3 Expert is a government program to reduce accidents and illnesses in the world of work, so as to increase work safety, profits and a positive image for the company. Occupational safety and health (K3) has become an important issue, not only on a national scale, but also on an international scale. Every company is required to implement K3 requirements. K3 no longer only belongs to companies in the oil and gas, mining, construction and manufacturing projects, but has spread to all types of companies. The profession in the field of K3 has become a promising profession for the next few decades. However, knowledge in the field of K3 is not mandatory only for employees in the field of K3, but is mandatory for all employees. Minister of Manpower Regulation No. 2 of 1992 has regulated the procedures for appointing General K3 Experts.